2003
DOI: 10.1002/bmc.254
|View full text |Cite
|
Sign up to set email alerts
|

Reversed‐phase liquid chromatographic method for the analysis of aminoglycoside antibiotics using pre‐column derivatization with phenylisocyanate

Abstract: A pre-column derivatization liquid chromatographic method has been developed for the analysis of aminoglycoside antibiotics using phenylisocyanate as a derivatization reagent. Derivatives including kanamycin, neomycin and gentamicin were formed by reaction of the analytes with phenylisocyanate in the presence of triethylamine. Phenylisocyanato groups were attached to corresponding amino groups of aminoglycoside and their molecular mass was confirmed by liquid chromatography-electrospray ionization-mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 11 publications
1
19
0
4
Order By: Relevance
“…A 0.5-mL volume of this solution was then mixed with 0.25 mL of a 0.5% v/v solution of triethylamine in acetonitrile, and 0.25 mL of a 0.5% v/v solution of phenylisocyanate in acetonitrile was added. Kim and others 20 reported that the reaction is very rapid at room temperature and the derivatives are stable for at least 24 h at room temperature. The phenylisocyanate and triethylamine reagents are also stable at room temperature for at least 24 h. 21 For citrate analysis, an isocratic ion-exchange HPLC method, as described in a Supelco application note, 22 was used.…”
Section: Hplc Assaysmentioning
confidence: 98%
See 2 more Smart Citations
“…A 0.5-mL volume of this solution was then mixed with 0.25 mL of a 0.5% v/v solution of triethylamine in acetonitrile, and 0.25 mL of a 0.5% v/v solution of phenylisocyanate in acetonitrile was added. Kim and others 20 reported that the reaction is very rapid at room temperature and the derivatives are stable for at least 24 h at room temperature. The phenylisocyanate and triethylamine reagents are also stable at room temperature for at least 24 h. 21 For citrate analysis, an isocratic ion-exchange HPLC method, as described in a Supelco application note, 22 was used.…”
Section: Hplc Assaysmentioning
confidence: 98%
“…For the gentamicin analysis, an isocratic reversed-phase HPLC method based on that of Kim and others 20 was followed, except for use of a 150 × 4.6 mm cyano column with a particle size of 4 µm (Jones, Hengoed, UK; lot 9650001) instead of a C18 column. The mobile phase consisted of acetonitrilewater-trifluoroacetic acid (400:600:1 v/v/v) at a flow rate of 1.0 mL/min.…”
Section: Hplc Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative proportion described from the standard compositions has permitted peak identification. Gentamicin C 1a , C 1 , C 2a and C 2 were identified by comparison of their retention time with those identified previously [16].…”
Section: Peak Assignmentmentioning
confidence: 99%
“…Concentrations of gentamicin components in plasma were assayed according to previously described method [16] with slight modification. The calibration and plasma samples of gentamicin were prepared by adding 200 µl of plasma to 300 µl of triethylamine solution (5 mg/ml in 90% acetonitrile and 10% water) to precipitate plasma protein.…”
Section: Sample Preparationmentioning
confidence: 99%